Mapping Knowledge Landscapes and Emerging Trends of the Links Between Bone Metabolism and Diabetes Mellitus: A Bibliometric Analysis From 2000 to 2021 - Cheng, Kunming; Guo, Qiang; Yang, Weiguang; Wang, Yulin; Sun, Zaijie; Wu, Haiyang (Frontiers in Public Health, 2022)
Background: Diabetes mellitus (DM) have become seriously threatens to human health and life quality worldwide. As a systemic metabolic disease, multiple studies have revealed that DM is related to metabolic bone diseases and always induces higher risk of fracture. In view of this, the links between bone metabolism (BM) and DM (BMDM) have gained much attention and numerous related papers have been published. Nevertheless, no prior studies have yet been performed to analyze the field of BMDM research through bibliometric approach. Methods: Articles and reviews regarding BMDM published between 2000 and 2021 were obtained from the Web of Science after manually screening. VOSviewer 1.6.16, CiteSpace V 5.8.R3, Bibliometrix, and two online analysis platforms were used to conduct the bibliometric and visualization analyses. Results: A total of 2525 documents including 2255 articles and 270 reviews were retrieved. Our analysis demonstrated a steady increasing trend in the number of publications over the past 22 years (R2 = 0.989). The United States has occupied the leading position with the largest outputs and highest H-index. University of California San Francisco contributed the most publications, and Schwartz AV was the most influential author. Collaboration among institutions from different countries was relatively few. The journals that published the most BMDM-related papers were Bone and Osteoporosis International. Osteoporosis and related fractures are the main bone metabolic diseases of greatest concern in this field. According to co-cited references result, “high glucose environment”, “glycation end-product” and “sodium-glucose co-transporter” have been recognized as the current research focus in this domain. The keywords co-occurrence analysis indicated that “diabetic osteoporosis”, “osteoarthritis”, “fracture risk”, “meta-analysis”, “osteogenic differentiation”, “bone regeneration”, “osteogenesis”, and “trabecular bone score” might remain the research hotspots and frontiers in the near future. Conclusion: As a cross-discipline research field, the links between bone metabolism and diabetes mellitus are attracting increased attention. Osteoporosis and related fractures are the main bone metabolic diseases of greatest concern in this field. These insights may be helpful for clinicians to recognize diabetic osteopenia and provide more attention and support to such patients.